ANALIS MINAT BELAJAR MAHASISWA PGSD PADA MATA KULIAH STRATEGI PEMBELAJARAN BERBASIS E-LEARNING - Fitri Siti Sundari; Elly Sukmanasa (Universitas Pakuan, 2018)
This research uses qualitative method with descriptive design. The purpose of this study is to identify the studentss learning interest in the courses of learning strategy based E-Learning. This research was conducted to the students of primary school teacher education in faculty of teacher training and education study program, Pakuan University, Bogor. The data source of this research is the lecturers of the subjects of learning strategy in the Primary School Teacher Education. Informants in this study are the students of the primary school teacher education which registered as active student for academic 2013/2014. The results showed that all indicators of learning interest is well achieved. The involvement scored 4.2. the attention scored 4.2; the interest scored 4.1; and happiness scored 4.3. Based on the results of the percent, the results of all learning interest indicators achieved more than 60% of the involvement score is 67% , the attention is 86%; the interest is 75% ; and happiness is the highest result. It got 90%.Keywords: learning interest, e-learning based learning strategy.